Implementasi Kebijakan Pengembangan Objek Wisata Watervang Di Kota Lubuk Linggau - Amelda, Suci; Sakir, Icuk Muhammad; Asteriniah, Femi (@-Publik: Jurnal Administrasi Publik, 2023)
This well-known Watervang Tourism Object is visited by many tourists. This Watervang tourist attraction is suitable for families, children, as well as young people to relax, fill holidays, or enjoy weekends. Facilities that are continuously equipped and perfected by the management, increase the interest of tourists to enjoy the charm of these tourist objects. According to (lubuklinggaukota.go.id) Tourist attractions in Lubuklinggau City are currently experiencing very good development, as evidenced by the large number of tourists arriving at the tourist attraction. Watervang. This cannot be separated from the announcement of Sebiduk Semare City in the "Let's Ngelong to Lubuklinggau 22:2:22" program. The issues addressed in this research involve insufficient financial allocation for the enhancement of water van tourism sites and a deficit in community engagement regarding the oversight of existing tourism assets. The study reveals that, on the whole, the implementation of the Watervang Tourism Object Development Policy in Lubuk Linggau City has been carried out competently. However, challenges persist in its execution, notably the inadequacy of funds for the development of watervang tourism sites and the limited involvement of the community in managing the available tourism resources.